Guidelines for Home-Based Physical Activities during COVID-19 Quarantine for People with Multiple Sclerosis: A Narrative Review - Hamid Mohtasham; Shahnaz Shahrbanian; Majid Mohtasham (Shiraz University of Medical Sciences, 2021)
Background: COVID-19 seems to have a major impact on physical activity behaviors, especially for people with Multiple Sclerosis (MS) who have healthconditions. Methods: This study was a narrative review. Six databases, namely PubMed, ISIWeb of Knowledge, Scopus, Google Scholar, Science Direct, and ProQuest, weresearch for relevant published studies.Results: Healthcare providers and organizations advise people to stay at home,but this does not mean that they should be inactive. Self-isolation has an adverseeffect on behavior activities and mental health in people with MS. Physical activity can act as medicine for people with MS, as it helps reduce stress, anxiety,and fatigue while improving balance, muscle strength, flexibility, and quality of life.Conclusion: People with MS are recommended to perform activities such as whole-body chair exercises with moderate intensity at least 150 minutes perweek according to the level of the individual's ability.